Literacy Activities at Islamic Boarding Schools in Banyumas Regency in the Perspective of Gordon Wells - Kholid Mawardi; Endang Sartika (Indonesian Academy of Social and Religious Research (IASRR), 2023)
Research on literacy activities at Islamic boarding schools is important because in terms of scientific development, learning at Islamic boarding schools is not only related to religious education but other knowledge including soft skills. This has significance in terms of accusations that Islamic boarding schools have significance for radicalism thinking because education is only focused on religious issues. The purpose of this study is to describe art and literacy activities in Islamic boarding schools throughout Banyumas Regency. The theory used is the literacy model of Gordon Wells which includes performative, functional, informational, and epistemic aspects. This research method is descriptive qualitative. The results showed: 1. There are 196 Islamic boarding schools in Banyumas Regency which are divided into 27 sub-districts; 2. Forms of literacy activities in Islamic boarding schools throughout Banyumas Regency include sermons, writing literary works, writing scientific reasoning, and acting; 3. Literacy levels in Islamic boarding schools throughout Banyumas Regency: performative relates to the reading and writing skills of Latin and Arabic pegon scripts, functional relates to the ability to bilingual between Javanese Ngapak and Indonesian, informative is the ability of the students to analyze information from readings and lectures, and epistemic in terms of creating new literacy both in the field of literature and acting which originates from the learning process